SARS-CoV-2 Infection after Effects: Multi-Organ Damage through Oxygen Radicals - Debatosh Datta; Rajveer Singh; Ravichandiran Velayutham; Arka Bhattacharya; Ujjwayini Ray; Sarbani Dasgupta; Soma Dutta; Aditi Saha; Debabrata Roy; Srinika Ghosh; Somasundaram Arumugam; Pallab Datta; et al. (Apollo Medicine)
Introduction: SARS-CoV-2 respiratory infection leads to two-layered pathology in time (a) immediate pathology and recovery or fatal ending and (b) long periods of remission followed by unexplained clinical expressions involving one or more systems with various clinical presentations, even leading to loss of lives. Among the common causative factors affecting nearly all organs and systems, oxygen radicals and oxygen-derived species (ROS) should rank conclusively on top. Objective: This clinical report, part of a community screening of unexplained clinical outcomes in post-COVID presentation, carries findings focusing on ROS production and possible ROS-induced damages. Materials and Methods: Flow cytometry was used to quantify the samples' total ROS, superoxide production, and apoptosis quantification. Results: Observations indicate unexplained nearly uniform enhanced ROS production in all these long COVID subjects, although clinical presentations varied from no complaints to the requirement of advanced interventions. Conclusion: Causative factors leading to raised oxygen-derived toxic intermediaries (ROS) in initiating these variable long COVID presentations are ill-understood yet possibly merit mass screenings and possible intense anti-oxidative therapy given that such antioxidant therapy through oral medications led to rapid lowering of ROS production and improvement of clinical presentations.